Emotion regulation and support mechanism in pre-service English teachers’school-based practicum - Sanjaya, Paschalis Kurniawan; Kuswandono, Paulus (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The school-based practicum constitutes a critical component of teacher education, affording pre-service teachers authentic pedagogical experiences within actual classroom environments. Notwithstanding the established implementation of the Teaching Practice Program (PLP) in Indonesia, scholarly inquiry into emotion regulation and support mechanisms within this context remains limited. This study therefore seeks to investigate the emotional challenges encountered by pre-service English teachers during their practicum, the strategies they employ to regulate these emotions, and the support mechanisms that facilitate this process. Guided by the following research questions: (1) How do pre-service English teachers regulate their emotions in response to the affective challenges encountered during the school practicum? and (2) What support mechanisms contribute to their emotional management and professional development? the research is theoretically framed by emotion regulation theory, emotional labor theory, and communities of practice theory. A qualitative phenomenological methodology was employed, utilizing semi-structured interviews for data collection. Findings indicate that pre-service teachers frequently experience negative affective states, including anxiety, self-doubt, stress, and frustration. In response, they deploy an array of regulation strategies, such as meticulous planning, cognitive reappraisal, attentional deployment, and situational suppression. The study further highlights the essential function of structured support systems, which provide crucial emotional and instrumental assistance through mentorship, constructive feedback, and collaborative engagement.